Hotel Vendome - Danielle Steel (Dell Mass Market Edition, 2012)
The hotel was old, run-down. But to Swiss-born hotelier Hugues Martin, it is a rough diamond tucked away on a quite New York City street. So Hugues scrapes together everything it into one of the world's finest luxury hotels.